1996
DOI: 10.1074/jbc.271.9.4961
|View full text |Cite
|
Sign up to set email alerts
|

FADD/MORT1 Is a Common Mediator of CD95 (Fas/APO-1) and Tumor Necrosis Factor Receptor-induced Apoptosis

Abstract: CD95 (Fas/APO-1) and tumor necrosis factor receptor-1 (TNFR-1) are related molecules that signal apoptosis. Recently, a number of novel binding proteins have been proposed to mediate the signaling of these death receptors. Here we report that an N-terminal truncation of one of these candidate signal transducers, FADD/MORT1, abrogates CD95-induced apoptosis, ceramide generation, and activation of the cell death protease Yama/CPP32. In addition, this dominant-negative derivative of FADD (FADD-DN) blocked TNF-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 684 publications
(90 citation statements)
references
References 33 publications
5
81
0
4
Order By: Relevance
“…In this study, the apoptotic response to Mith was accompanied by activation of a mitochondria-mediated apoptotic pathway through DR5/caspase-8 signaling. This phenomenon might also explain in part how Mith increases cell sensitivity to TNF-α31, as caspase-8 is implicated in TNF-mediated and death receptor-mediated apoptotic pathways40. Several regulators and effectors controlling the DR5-mediated apoptotic pathway might be involved in Mith-induced apoptosis.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, the apoptotic response to Mith was accompanied by activation of a mitochondria-mediated apoptotic pathway through DR5/caspase-8 signaling. This phenomenon might also explain in part how Mith increases cell sensitivity to TNF-α31, as caspase-8 is implicated in TNF-mediated and death receptor-mediated apoptotic pathways40. Several regulators and effectors controlling the DR5-mediated apoptotic pathway might be involved in Mith-induced apoptosis.…”
Section: Discussionmentioning
confidence: 98%
“…Based on the existence of one of two distinct domains, the TNF-R superfamily members are divided into two subgroups, the death domain (DD)-containing receptors and TNF-R-associated factor (TRAF) interacting receptors [48]. The apoptotic cell death pathway is activated following recruitment of the Fas-associated death domain (FADD/MORT) protein to TRADD through interaction of the death domains (DD) [49]. FADD subsequently leads to activation of caspases and the release of pro-apoptotic factors from mitochondria to sustain the apoptotic signal [50] (Fig.…”
Section: Apoptosis Signaling Pathways In Hepatocytesmentioning
confidence: 99%
“…These studies supported the hypothesis that DR signaling via Fas/FasL is crucial to the maintenance of lymphocyte homeostasis. It was thus surprising that mice lacking the function of FADD [59, 60], an essential signaling adaptor required for DR-induced apoptosis [61], failed to develop lymphoproliferative disease [6264]. Subsequent investigation also revealed that loss of casp8, normally recruited to the death inducing signaling complex (DISC) via FADD following DR stimulation [10, 11, 60, 65], similarly failed to cause lymphoproliferative disease in humans and mice [15, 66].…”
Section: 4 T/b Cell Caspase 8 – Activation Pathwaymentioning
confidence: 99%